The Role of Trust and Data Sharing Willingness in Users’ Acceptance of Insurance Telematics - Tian, Xiaoguang; Liu, Xiaotong (Journal of Knowledge Management Practice, 2024)
Understanding customers’ attitudes toward insurance telematics can significantly affect knowledge management practices within the insurance industry. This study explores the factors affecting users’ acceptance of insurance telematics. A theoretical adoption model was proposed by extending the technology acceptance model and theory of planned behavior with a priorly proved construct trust and a new construct data sharing willingness (DSW). Trust is built upon perceived usefulness, ease of use, and DSW in this research. The findings display that trust is crucial in increasing a positive feeling toward insurance telematics, which affects users’ acceptance of insurance telematics, along with subjective norms. DSW was found to impact users’ level of trust significantly. Theoretically, these findings imply that trust offers a significant passage for factors influencing consumers’ adoption of technology. Practically, the findings shed light on assisting the auto insurance industry in its digital transformation and designing interventions to improve consumers’ adoption of insurance telematics. The authors also suggest regulators take actions to oversee the technology to ensure customer privacy protection and fair market competition.
Keywords: knowledge management; digital transformation; insurance telematics; technology adoption; trust; privacy